Ocular adverse events associated with immune checkpoint inhibitors: a novel multidisciplinary management algorithm. (February 2021) - Shahzad, Orthi; Thompson, Nicola; Clare, Gerry; Welsh, Sarah; Damato, Erika; Corrie, Philippa
Ocular immune-related adverse events (IrAEs) associated with use of checkpoint inhibitors (CPIs) in cancer therapeutics are relatively rare, occurring in approximately 1% of treated patients. Recognition and early intervention are essential because the degree of tissue damage may be disproportionate to the symptoms, and lack of appropriate treatment risks permanent loss of vision. International guidelines on managing ocular IrAEs provide limited advice only. Importantly, local interventions can be effective and may avoid the need for systemic corticosteroids, thereby permitting the continuation of CPIs. We present a single institution case series of eight affected patients managed by our multidisciplinary team. Consistent with previously published series and case reports, we identified anterior uveitis as the most common ocular IrAE associated with CPIs requiring intervention. Based on our experience, as well as published guidance, we generated a simple algorithm to assist clinicians efficiently manage patients developing ocular symptoms during treatment with CPIs. In addition, we make recommendations for optimising treatment of uveitis and address implications for ongoing CPI therapy.